(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
A wide range of unusual foreign bodies in the bladder has been reported in the literature. The urethra is the main entrance if the foreign body is inserted into the urinary tract. We present a report regarding a Hindu male aged 16 years, who was admitted in the Urology Department of S.P. Medical College and Associated Group of Hospital, Bikaner, on 3.12.2007 with complaints of pain in the lower abdomen and blood in urine. The X-ray examination revealed a foreign body in the urinary bladder, which was removed by an urologist. The case was referred to a psychiatrist, who took the patients into confidence and diagnosed him as case erotogenic masochism.